Investigation into possible mechanisms of light pollution flashover of 275kv transmission lines as a cause of unknown outages - Kleinhans, Kevin (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2005.